Workloads applied in development of strength and speed endurance within a four year long training cycle of advanced female junior canoeists - Rynkiewicz, T.; Starosta, W. (Polish Journal of Sport and Tourism, 2009)
The purpose of this research was to: 1. Determine the magnitude of workloads applied in development of strength and speed endurance within a four year training cycle of female junior canoeists. 2. Determine the dominating methods and means of training applied in training of young female canoeists, and their influence on the effectiveness of the training. The research covered training workloads of five female junior competitors - students of Sports Championship School. At the time of commencement of the research they were at the age of 15, their average height was 167 cm, average body mass 60 kg at the beginning and 64 kg after the end of the research. The effectiveness of the training oriented on development of strength and speed endurance was tested based on the magnitude of workload in endurance run as well as in exercises with weights. Their number was expressed in terms of annual cycles and subsequent months of each cycle. The speed of paddling over the tested distances was measured on single seat kayaks during competitions. In the assessment of strength training we determined the proportions between the basic means of the training. The intensiveness of running training was described by means of number and average lengths of the so called "tempo sections". Based on the research it was discovered that a three year cycle was applied in the training of female junior canoeists. This cycle resulted from the coach`s desire to obtain best results (at the age of 18) during official competitions, in which the Polish national team participated. This type of training was characterised by a significant degree of effectiveness, which however did not ensure any significant results at mature age. Bearing in mind the contemporary knowledge, one can doubt if large workload was the appropriate way to develop maximum strength of the tested female canoeists. This manner of training can cause lowering of the strength, time and spatial differentiation of movements, and especially the strength accuracy, which is essential for efficient paddling.